Pencegahan kecurangan (fraud) di Pondok Modern Gontor - M Alif Nur Irvan; Maulidyati Aisyah (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
Fraud is an illegal act or activity done intentionally or unintentionally and its nature can harm many parties. The purpose of this study is to determine the influence of Islamic behavior, Islamic environment to internal control system compliance in preventing intention to commit fraud. This research was using a questionnaire. Participants in this research are teachers (ustadz) who work in business unit of Pondok Modern Darussalam Gontor as many as 100 respondents. Data was analyzed by Structural Equation Model. Results show that Islamic behavioral and Islamic environment variables positively influence internal control system compliance which eventually negatively affect the intention to commit fraud. This implies that the effectiveness of internal control is more on the compliance of the people around it no matter how simple it is. Results also assure that the model applied in Pondok Modern Gontor has been succeed in developing behavior and environment which prevent fraudulent actions.